Vanillic acid attenuates H2O2-induced injury in H9c2 cells by regulating mitophagy via the PINK1/Parkin/Mfn2 signaling pathway - Mei, Manxue; Sun, Haoxiang; Xu, Jiayu; Li, Yimeng; Chen, Guiling; Yu, Qihua; Deng, Changsheng; Zhu, Wei; Song, Jianping (Frontiers in Pharmacology, 2022)
Vanillic acid, a phenolic compound mainly obtained from the foot of Picrorhiza scrophulariiflora Pennell, has been demonstrated to possess cardiovascular protective effect in previous studies. However, there is a lack of research on vanillic acid protecting cardiomyocytes from oxidative stress injury by mediating mitophagy. In the present study, the oxidative stress injury in H9c2 cell line was induced by H2O2. Our results confirmed that vanillic acid mitigated apoptosis and injury triggered by oxidative stress, evidenced by the decline production of reactive oxygen species, malondialdehyde and level of lactate dehydrogenase, and the increase of superoxide dismutase and glutathione. The use of vanillic acid could also improve the polarization of mitochondrial membrane potential and decreased the cellular calcium level. After treatment of vanillic acid, impaired autophagy flux and mitophagy were improved, and mitochondria restored its slender in morphology and function. vanillic acid increased the expression of PINK1, parkin, Mfn2 and the ratio of LC3-II/LC3-I, and decreased the expression of p62.But under the intervention of mitophagy inhibitor 3-MA, vanillic acid could not change the expression of PINK1/Parkin/Mfn2 and downstream genes to affect cell autophagy, mitophagy and mitochondrial function.Our findings suggested that vanillic acid activated mitophagy to improve mitochondrial function, in which PINK1/Parkin/Mfn2 pathway could be the potential regulatory mechanism.